Scouting an Anthropology of Sport - Moore, Philip (Anthropologica, 2022)
This paper explores some of the processes that shape the development of an anthropology of sport. It situates the anthropology of sport in relation to a broad and eclectic field of sport studies. It then identifies the anthropology of sport as embedded in the particular sorts of ethnographic projects under taken and the sites where they are undertaken. Finally, it explores the significance of teaching and researching as activities that contribute to the shaping of an anthropology of sport. The paper argues for a disciplinary commitment to anthropology coupled with an acknowledgement that we should be extending our reach beyond the current boundaries of our discipline. Rather than writing only for a narrowly defined anthropology of sport we should be actively engaging broader and more inclusive audiences interested in sporting activities.